Efeito do processamento e da frequência alimentar para tilápias do Nilo (Oreochromis niloticus) durante a alevinagem - Fava, Aldo Felipe (2021)
This study aimed to determine the best way of processing diets and feeding frequency for the Nile tilapia (Oreochromis niloticus) fingerlings, by evaluating water quality, zootechnical performance, proximate composition, liver and muscle histology, and partial economic analysis. For this, two experiments were carried out. In the first, 250 tilapia fingerlings with an average initial weight of 0.975 g were used, distributed in 25 experimental boxes. The randomized experimental design consisted of five treatments and five replications. The treatments were: ME1 – 1 mm microextruded feed; ED03 - extruded and crumbled feed 0.3 mm; ED06 - extruded and crumbled feed 0.6 mm; BF03 – mash feed 0.3 mm and BF06 – mash feed 0.6 mm. The rations were formulated in order to meet the requirements of the species at this stage. The animals were fed six times a day (8:00 am; 10:00 am; 12:00 pm; 2:00 pm; 4:00 pm and 6:00 pm) until apparent satiety. In the second experiment, the ideal feeding frequency for the diet that provided better results in experiment 01 was evaluated. For this, 240 fingerlings with an average initial weight of 0.793 g were used, distributed in 24 experimental boxes. The experimental design was completely randomized and six feeding frequencies (4 (F4), 5 (F5), 6 (F6), 7 (F7), 8 (F8) and 9 (F9) times a day were evaluated with four repetitions. In both experiments, water quality parameters such as pH, dissolved oxygen (mg /L-1), electrical conductivity (µS / cm-1) and temperature (°C) were checked weekly, and water samples were collected from the experimental units for subsequent analyzes of total phosphorus (PT) and total nitrogen (NT). At the end of the experimental periods, the animals were fasted for 12 hours, were anesthetized, weighed and measured to determine the zootechnical parameters. Materials were also collected to determine the proximate composition and for histological analysis of the liver and muscle. For economic analysis, the costs related to fish and food were considered to determine the partial net income. In experiment I the feed conversion (CA) was significantly lower in EM1 (1.17) compared to the highest value of 1.95 in ED03. Although higher in EM1, the weight gain in this treatment (9.26 g) did not differ from ED06. The protein retention coefficient was statistically higher in EM1 (36.47%). In water quality, EM1 resulted in the lowest levels of NT (0.94 mg / L-1) and PT (0.45 mg /L-1), while BF03 showed the highest values of 2.27 and 0.91 mg L-1 of NT and PT, respectively. The proximate composition of fingerlings did not differ between treatments. Fish fed with microextruded diet with 1 mm in diameter showed the best results in zootechnical performance, in addition to reduced impact on water quality. Partial net revenue (RLP) was higher in EM1. In experiment II, it was possible to observe significant differences (p<0.05) for weight gain, which was higher in F5 (9.13 g) and F6 (9.27 g), however, the feed conversion did not differ ( P>0.05) between treatments. The N and P contents, although they were lower in F4, resulted from the lower growth. The diameter of muscle fibers indicated hyperplasia in all treatments, with a prevalence of fibers between 10 and 20 micrometers in F4, F5, F6 and F7 and between 30 and 40 for F8 and F9. The perimeter and area of the hepatocytes differed only between F5 and F9, while the volume, perimeter and area of their nucleus did not differ. Partial net revenue (RLP) was higher in F6 (USD 7.35) followed by F5 (USD 7.22), the small margin favors F5 due to the lower need for daily meals. In conclusion, although microextruded feed (EM1) has the highest cost, had the best zootechnical and economic performance, in addition to reduced impact on water quality, it, offered between 5 to 6 times a day, has the best economic, zootechnical and histological performance.